2021
DOI: 10.1155/2021/4618352
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Chinese Herbal Medicine Plays a Role in the Liver, Kidney, and Intestine to Ameliorate Hyperuricemia according to Experimental Studies

Abstract: In the last few decades, hyperuricemia has drawn increasing attention owing to its global prevalence. Observational surveys have manifested that there is a relation between hyperuricemia and increased risks of hypertension, chronic kidney disease, cardiovascular events, metabolic disorders, end stage renal disease, and mortality. As alternatives, Traditional Chinese medicinal herbs have demonstrated concrete effects in mitigating hyperuricemia in different experiments. Researchers have made efforts to investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…In addition, HUA leads to an inflammatory response and triggers the secretion of related inflammatory cytokines, including TNF-α, IL-1β and IL-6. 20,46 Our results showed that BBR and STC@BBR-SANPs significantly decreased the elevation of IL-1β, IL-6 and TNF-α (Figure 10C-E). Meanwhile, STC@BBR-SANPs (P < 0.01) tended to be superior to BBR (P < 0.05) in IL-6.…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…In addition, HUA leads to an inflammatory response and triggers the secretion of related inflammatory cytokines, including TNF-α, IL-1β and IL-6. 20,46 Our results showed that BBR and STC@BBR-SANPs significantly decreased the elevation of IL-1β, IL-6 and TNF-α (Figure 10C-E). Meanwhile, STC@BBR-SANPs (P < 0.01) tended to be superior to BBR (P < 0.05) in IL-6.…”
mentioning
confidence: 78%
“…PO and HX were given to all groups to induce HAU model as previously reported. 20 As shown in Figure 2A and B , the HUA model was modified according to the preliminary experiment. 29 Briefly, all mice except control group were treated intraperitoneally (i.p.)…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduced excretion of uric acid causes abnormalities in the renal system [ 118 ]. A treatment strategy for gout and hyperuricemia includes the use of Cortex Fraxini , which is a well-known traditional Chinese herbal medicine [ 119 ]. A study by Wang et al performed a comparative study on plasma of an orally treated normal and hyperuricemic male Sprague Dawley rats with Cortex Fraxini using UPLC-MS/MS method.…”
Section: Detection Pharmacokinetic and Metabolic Studies Of Esculetinmentioning
confidence: 99%
“…Traditional Chinese medicine (TCM) is a unique health care resource in China, exhibiting great therapeutic potential in diverse aspects of human diseases. Evidence has established that many TCMs are beneficial to the treatment of hyperuricemia (Xu et al, 2021). For example, Tufuling granules decrease the UA level and inhibit the inflammatory response in hyperuricemic rats (Wu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%